Wrażliwość a socjalny wymiar praw gwarantowanych w art. 2, 3 i 8 Europejskiej Konwencji Praw Człowieka - Hernandez-Połczyńska, Anna (PRAWO i WIĘŹ, 2026)
The European Convention on Human Rights primarily protects civil and political rights; however, according to the European Court of Human Rights, its interpretation “may extend into the sphere of social and economic rights.” This paper aims to analyse the relationship between the applicant’s status as vulnerable or as belonging to a vulnerable group, and the extension of the Convention’s protection into the domain of social rights. The research focuses on judgments and decisions of the ECtHR concerning the social dimension of rights enshrined in Articles 2, 3 and 8 of the Convention, in which the concept of vulnerability is invoked. The paper examines how the Court applies the concept of vulnerability and assesses its impact on the outcome of the case.